Leptin and Obesity: Role and Clinical Implication - Obradovic, Milan; Sudar-Milovanovic, Emina; Soskic, Sanja; Essack, Magbubah; Arya, Swati; Stewart, Alan J.; Gojobori, Takashi; Isenovic, Esma R. (Frontiers in Endocrinology, 2021)
The peptide hormone leptin regulates food intake, body mass, and reproductive function and plays a role in fetal growth, proinflammatory immune responses, angiogenesis and lipolysis. Leptin is a product of the obese (ob) gene and, following synthesis and secretion from fat cells in white adipose tissue, binds to and activates its cognate receptor, the leptin receptor (LEP-R). LEP-R distribution facilitates leptin’s pleiotropic effects, playing a crucial role in regulating body mass via a negative feedback mechanism between adipose tissue and the hypothalamus. Leptin resistance is characterized by reduced satiety, over-consumption of nutrients, and increased total body mass. Often this leads to obesity, which reduces the effectiveness of using exogenous leptin as a therapeutic agent. Thus, combining leptin therapies with leptin sensitizers may help overcome such resistance and, consequently, obesity. This review examines recent data obtained from human and animal studies related to leptin, its role in obesity, and its usefulness in obesity treatment.